2010
DOI: 10.1021/bm101149r
|View full text |Cite
|
Sign up to set email alerts
|

Co-Electrospun Blends of PLGA, Gelatin, and Elastin as Potential Nonthrombogenic Scaffolds for Vascular Tissue Engineering

Abstract: In search for novel biomimetic scaffolds for application in vascular tissue engineering, we evaluated a series of fibrous scaffolds prepared by coelectrospinning tertiary blends of poly(lactide-co-glycolide) (PLGA), gelatin, and elastin (PGE). By systematically varying the ratios of PLGA and gelatin, we could fine-tune fiber size and swelling upon hydration as well as the mechanical properties of the scaffolds. Of all PGE blends tested, PGE321 (PLGA, gelatin, elastin v/v/v ratios of 3:2:1) produced the smalles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
105
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 53 publications
2
105
0
3
Order By: Relevance
“…11,38 Moreover, various synthetic and natural materials can be blended into nanocomposite electrospun scaffolds, observably improving cell-scaffold interactions for tissue engineering applications. [16][17][18] The GT/PCL membrane is a representative nanocomposite electrospun scaffold blend composed of the natural material gelatin and the synthetic polymer PCL, and has been widely used for engineering diverse tissues, including nerve, bone, skin, cardiovascular, and cartilage. 16,20,[39][40][41] Our previous studies have further modified the fabrication of GT/PCL membranes to obtain finer and compositionally homogeneous hybrid nanofibers, and have demonstrated that …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,38 Moreover, various synthetic and natural materials can be blended into nanocomposite electrospun scaffolds, observably improving cell-scaffold interactions for tissue engineering applications. [16][17][18] The GT/PCL membrane is a representative nanocomposite electrospun scaffold blend composed of the natural material gelatin and the synthetic polymer PCL, and has been widely used for engineering diverse tissues, including nerve, bone, skin, cardiovascular, and cartilage. 16,20,[39][40][41] Our previous studies have further modified the fabrication of GT/PCL membranes to obtain finer and compositionally homogeneous hybrid nanofibers, and have demonstrated that …”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In our previous study, we fabricated electrospun gelatin/ polycaprolactone (GT/PCL) nanofibrous membranes, and found that acetic acid could improve the miscibility, contributing to obtaining finer and compositionally homogeneous hybrid nanofibers. 19 Furthermore, GT/PCL membranes seeded with chondrocytes in a sandwich model could form good-quality cartilage with precise three-dimensional (3-D) structures.…”
mentioning
confidence: 99%
“…Biodegradable polymers, such as poly(L-lactic acid) (PLLA), poly(glycolic acid) (PGA) and poly(lactic-co-glycolic acid) (PLGA), have drawn a lot of attention in research because of their well-characterized biodegradable properties [24][25][26][27][28]. These materials have been successfully used in bone tissue, vessel, and patches for wounds [29][30][31]. Among these biodegradable polymers, PLGA is one of the most widely used classes of polymers for vascular tissue engineering, which has been already approved by the Food and Drug Administration (FDA) as a constituent of many biomaterial-based devices [28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a new technique to combine the outer and inner layers with the intermediate layer, PLGA-gelatin, has been developed in this study. Fortunately, electrospun PLGA-gelatin showed excellent smooth muscle cell proliferation [23]. The concept of using a combination of natural and synthesized polymers for forming three layers to mimic a natural blood vessel was investigated by Wang et al [22] using a PLGA-sandwiched cell/fibrin hydrogel.…”
Section: Introductionmentioning
confidence: 99%